A Study of Total Maximum Daily Load (TMDL) by Using Water Quality Modelling as an Approach to Investigate the Quality of Water at Bentayan River, Muar - Anis Adibah Anuar Alsadat,; MAIZZATY, NOR MAIZZATY BINTI ABDULLAH; Hasnida Harun, (Progress in Engineering Application and Technology, 2024)
This study evaluates the water quality of the Bentayan River in Muar, Malaysia, by integrating the Total Maximum Daily Load (TMDL) framework and water quality modeling using QUAL2K. The research aims to determine the current state of the river’s health and assess the impact of industrial and urban activities on key water quality parameters. Field data were collected from five strategic checkpoints along the river, focusing on parameters such as pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), and total suspended solids (TSS). Laboratory analyses revealed significant pollutant levels, particularly high BOD and TSS at Checkpoint 4, an area with dense industrial activity. Conversely, the highest DO levels were observed at Checkpoint 1, which exhibited the largest discharge rate, indicating better water quality. The QUAL2K model was calibrated with the collected data, demonstrating its effectiveness in simulating the river's conditions under varying scenarios, including tidal influences. The TMDL calculations identified the maximum allowable pollutant loads that ensure compliance with water quality standards. This approach provided a basis for recommending pollution reduction strategies and regulatory measures to enhance the river's ecological health. The findings highlight the critical need for ongoing monitoring and the implementation of effective management practices to mitigate pollution and preserve the Bentayan River's environmental and economic roles. This study underscores the value of integrating TMDL and water quality modeling as robust tools for river management and sustainable development.